The Influence of Employee Competence, Work Ethic, and Work Discipline on Public Service Quality (Taxpayer Perception Study at the Semarang I UPPD Samsat Office) - Ar Rahman, Muhammad Irfan; Bagana, Batara Daniel (Majapahit Journal of Islamic Finance and Management, 2025)
Public service delivery reflects the performance of the bureaucracy, which in turn influences public trust in the government. However, it is still perceived as suboptimal. This study focuses on evaluating the influence of three key aspects namely, human resource competence, ethical principles in the workplace, and employee discipline, on the quality of public services within the UPPD Samsat Semarang 1 office. A quantitative approach was employed using a survey method, with purposive sampling applied to select 100 taxpayers as respondents. The collected data were analyzed using multiple linear regression techniques. The results indicate that all independent variables exhibit a significant and positive correlation with public service quality. Among these, employee discipline emerged as the most influential factor in enhancing service quality. These findings align with Weber’s theory of bureaucracy and underscore the critical importance of effective human resource management in the public sector. This study contributes to the ongoing efforts to improve public service delivery by emphasizing professionalism, efficiency, and humanistic values in the administration of motor vehicle tax services. It also serves as a reference for future policy development aimed at enhancing the quality of public services.